International academic mobility across space and time: The case of Indian academics - Czaika, M; Toma, S (Wiley, 2017)
Internationalization has become a central feature of academic careers as academics are increasingly expected to be mobile. Yet we still know relatively little about the actual patterns and drivers of academic mobility across space and time. Using unique data from a recent survey of around 4,600 Indian academics across the globe, this article examines the dynamics of international academic mobility among one of the largest global academic diasporas. Overall, we find a strong ‘path-dependency’ of academic career and mobility trajectories, demonstrating the considerable importance of prior career steps in shaping future mobility choices. Working abroad as an academic, particularly in an Anglo-Saxon destination, becomes very unlikely without some early international study experience. However, contextual and individual-level factors may moderate this path-dependency. Younger generations of Indian researchers, men, high-performing students and those with (Indian) degrees that are more valued internationally, have higher chances of breaking the path. In addition, socioeconomic background seems to be an important driver for early career and mobility steps but becomes much less relevant for future academic employment.